Ultrastructure of spermatozoa of members of Calappidae, Aethridae and Menippidae and discussion of their phylogenetic placement - Camargo, Tavani Rocha [UNESP]; Wolf, Milena Regina [UNESP]; Mantelatto, Fernando L.; Tudge, Christopher; Zara, Fernando José [UNESP] (Wiley, 2018)
The families Aethridae and Calappidae were originally considered as part of the same family; however, their morphology and molecular biology separate them into two families. In this context, we describe the ultrastructure of spermatozoa of species of the Calappidae, Aethridae and Menippidae to elucidate the relationships among taxa. The vasa deferentia were submitted to routine protocols for transmission electron microscopy. Our results indicate that the morphology of the spermatozoa of Hepatus pudibundussupports its exclusion from the Superfamily Calappoidea due to the presence of the apical striated layer. The spermatozoa of Menippe nodifrons is very similar to H. pudibundus and corroborates the recent phylogenetic analysis using sequence data of nuclear genes. Moreover, our results evidence two morphological patterns of spermatozoa within Calappidae. Calappa ocellata and C. cinerea show spermatozoa with a wide acrosome vesicle, a thick operculum shaped as a shallow “W” and a large thickened ring. Calappa gallusand C. hepatica show spermatozoa with a longer acrosome vesicle, a pointed operculum and a slender thickened ring. Our ultrastructure results conform with previous molecular proposal and show that spermatozoa ultrastructure can be an effective tool to adjust phylogenetic relationship when used in association with molecular data.
Keywords: Brachyura; crab; Decapoda; transmission electron microscopy